PENGARUH KONSENTRASI BASA TERHADAP PRODUK HIDROLISIS ESTER - Saragih, Sri Wahyuna (BIOLINK (Jurnal Biologi Lingkungan, Industri, Kesehatan), 2015)
This study aims to determine the effect of concentration of base to ester hydrolysis products. Ester can dihidroisis with an alkaline catalyst at different concentrations. In this study, the concentration of metal acetate used was 1 M NaOH while coud concentration was 0.5 M, 0.75 M, 1 M, 1.25 M. The hydrolysis reaction using ethanol and refluxed for 2 hours at room temperature. Hydrolysis of methyl acetate ester compounds produced methanol with purity varies by different concentrations of methyl acetate and NaOH. At concentrations of 0.5 M NaOH acquired 79.5068% purity methanol, 0.75 M NaOH concentration 85.6665% purity methanol, 1 M NaOH concentration 99.6311% purity methanol and NaOH concentration of 1.25 M purity methanol 100,0000 %. Based on the results of the hydrolysis product purity shows the influence of the concentration of NaOH to the product ester hydrolysis. Methanol compound structure was analyzed by an infrared spectrometer and a mass spectrometer.